Hungarian Monitoring, 25 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Portrait of new Polish head of government and other reports - First meeting of former Soviet camp inhabitants in the USSR - GDR evangelical church urges East German citizens to stay in the country Domestic Affairs: - M. Németh and Gy. Horn pay lightning visit to West German to meet Chancellor Kohl and Foreign Minister Genscher - Hungarians detained in Prague - Opposition roundtable discussions - Presidential Council today permitted religious orders to function - Flood of GDR refugees - Gabčíkovo-Nagymaros dam - Petition for recall of parliamentary representative Gy. Aczél - Hungarian book distribution at rock bottom levels Economy: - Hungarian National Bank would like to take up USD 2.3 billion worth of foreign loans this year Külpolitika: - Lengyelország: az új kormányfő portréja, egyéb beszámolók - Első találkozó a volt szovjet lágerek lakóival a SZU-ban - Az NDK evangélikus egyháza maradásra szólítja fel az NDK polgárokat Belpolitika: - Németh M. és Horn Gy. villámlátogatáson az NSZK-ban H. Kohl kancellárral és Genscher külügyminiszterrel - A Prágában fogvatartott magyarok ügye - Ellenzéki Kerekasztal tárgyalások - Az Elnöki Tanács mai ülésén engedélyezte a szerzetesrendek működését - NDK-s menekült áradat - Bős-nagymarosi vízlépcső - Aláírásgyűjtés Aczél Gy. országgyűlési képviselő visszahívására - Padlón a magyar könyvterjesztés Gazdaság: - A Magyar Nemzeti Bank az idén 2 milliárd 300 millió dollár értékben szeretne felvenni hitelt külföldről